Late Eocene volcanism in North Patagonia (42°30′–43°S): Arc resumption after a stage of within-plate magmatism - Fernández Paz, Lucía (2018)
Mid-Cenozoic widespread arc magmatism in North Patagonia extends from the forearc to the retroarc zones, representing an anomalous large volume when compared to the present-day arc zone and even other past arc configurations. It represents a crucial stage in Andean arc evolution as was developed after a period of arc waning and within plate magmatism. Controversies exist regarding the origin of these volcanic sequences, with scarce integrated field, geochemical and geochronological analyses. We focused our study on the El Maitén Belt, located in the present-day retroarc zone, particularly on a poorly studied section corresponding to the southern outcrops of this volcanic belt. This volcanism consists of basaltic and andesitic lava flows and interbedded pyroclastic deposits, whose emplacement was controlled by extensional tectonics as indicated by the occurrence of wedge-like strata associated with normal faults. A U-Pb age on the basal part of this section shows that magmatic activity started by 37 Ma, earlier than previous studies that considered this volcanism as Oligocene. Geochemically, these rocks are part of the subalkaline and particularly tholeiitic series. All samples show trace element enrichments, depletions and ratios characteristic of arc magmas, though fluids and sediment imprint seem limited. On these bases, we propose decompression melting as the main process associated with the genesis of this volcanism. Therefore, this magmatic association constrained to the late Eocene represents the earliest evidence of arc volcanism in the Patagonian Andes, under an extensional regime, after a Paleogene waning of arc activity.